HPV Vaccine Coverage Among Adolescent Males in Ohio: Results of a Longitudinal Study - Andreas A. Teferra; Brittney Keller-Hamilton; Megan E. Roberts; Paul L. Reiter (Ohio Journal of Public Health, 2019)
Background: Human papillomavirus (HPV) vaccine has been recommended for males in the United States since 2011, yet little is known about vaccine coverage among adolescent males in Ohio. Our longitudinal study examined HPV vaccine coverage among adolescent males in Ohio and identified predictors of vaccination. Methods: The Buckeye Teen Health Study recruited adolescent males aged 11 to 16 years and their parents from 1 urban county and 9 rural counties in Ohio. We report longitudinal vaccination data on 1126 adolescent males, with baseline data from 2015-2016 and follow-up data from 2017-2018. We used multivariable Poisson regression to identify predictors of HPV vaccine initiation that occurred between baseline and follow-up. Results: At baseline, 42.4% of parents reported their sons had initiated the HPV vaccine series. Among parents whose sons were unvaccinated at baseline, 36.3% indicated initiation at follow-up. Initiation at follow-up was more com-mon among sons who had received influenza vaccine (RR = 1.54, 95% CI = 1.08-2.18) or whose parents indicated lack of a recent visit to a doctor as the main reason for not yet vaccinating at baseline (RR = 1.41, 95% CI = 1.02-1.95). Initiation was less common among sons whose parents had an associate degree or some college education (RR = 0.28, 95% CI = 0.46-0.99). Main reasons for not vaccinating changed from baseline to follow-up among parents of unvaccinated sons. Conclusion: Although HPV vaccine initiation increased over time, many adolescent males in Ohio remain unvac-cinated. Findings can help guide future strategies for increasing HPV vaccine coverage among this population.
Keywords: Adolescent males; HPV vaccine; Parents; Longitudinal